Analisis Perancangan Dinding Penahan Tanah Untuk Seawater Intake Pembangkit Listrik Tenaga Uap - Adz Dzikro, Ibadurrahman; Mades Aweka, Sarah Via; Amani, Azka Syarifa; Jayanti, Harum Kurnia; Sahadewa, Andika (Institut Teknologi Bandung, 2024)
Abstract The handling of retaining walls in the PLTU seawater intake project is a crucial part in maintaining the stability of buildings below ground level. The retaining wall construction is selected based on the depth of excavation, soil type, the height of the Groundwater Table (GWT), and the load being retained. The lateral force calculation method uses Rankine and Coulomb theories with specified soil parameters. The case study was conducted at the seawater intake area of Java 9 & 10 Suralaya PLTU in Suralaya, Cilegon, Banten. The design process involved soil data interpretation, site class determination, and stability analysis using MIDAS GTS NX software. The retaining wall design is divided into two parts, using diaphragm walls and secant piles. The use of lateral reinforcement in the form of soil anchors is adjusted to the provisions of SNI 8460-2017. The design results show that the wall and anchor configurations meet the design criteria, with appropriate values of safety numbers and lateral deflections. However, the selection of Mohr-Coulomb soil model and pseudostatic earthquake analysis produced more conservative results. In conclusion, the retaining wall design proved to be effective in handling the lateral soil loads and pressures in the seawater intake PLTU project.